INTEGRATION PLATFORM AS CENTRAL SERVICE OF DATA REPLICATION IN DISTRIBUTED MEDICAL SYSTEM - Wajs, Wiesław; Rączka, Krzysztof; Stoch, Paweł; Kruczek, Piotr (Computer Science, 2013)
The paper presents the application of Java Integration Platform (JIP) to data replicationin the distributed medical system. After an introductory part on the medical system’s architecture,the focus shifts to a comparison of different approaches that exist with regard totransferring data between the system’s components. A description is given of the historicaldata processing and of the whole area of the JIP application to the medical system.